Gender-based abuse: the global epidemic Violência e genêro: uma epidemia global - Lori Heise (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1994)
Gender Based violence-including rape, domestic violence, murder and sexual abuse-is a profund health problem for women across the globe. Although a significant cause of female morbidity and mortality, violence against women has only recently begun to be recognized as an issue for public health. This paper draws together existing data on the dimensions of violence against women worldwide and reviews available literature on the health consequences of abuse. It argues that the health sector has an important role to play in combatting violence against women through increased research, screening and referral of victims, and behavioral interventions. Any strategy to confrnt violence must address the root causes of abuse in addition to meeting the immediate needs of victims. This means challenging the social attitudes and beliefs that undergird men's violence and renegotiating the balance of power between women and men at all levels of society. Violência baseada no gênero, incluindo seqüestros, violência doméstica, homicídios e abuso sexual, é problema profundo de saúde para a mulher em todo o mundo. Embora sendo uma causas significativa de morbi-mortalidade, a violência cintra as mulheres só recentemente foi reconhecido como objeto de Saúde Pública. Este trabalho reune dados existentes sobre dimensões da violência contra as mulheres no mundo e revê a literatura sobre as conseqüências das abusos sobre a saúde. Argumenta-se que o setor tem importante papel no combate à violência contra a mulher, através do desenvolvimento de pesquisas, notificação, organização de serviços de referência para as vítimas e para propostas de intervenção. Qualquer estratégia para confrontar a violência necessita ser dirigida para as raízes dos abusos, além, evidentemente, de atender às necessidades imediatas das vítimas. Isto significa desafiar atitudes e crenças sociais que fundamentam a violência dos homens contra as mulheres e criar formas de negociação do poder entre os gêneros, em todos os níveis da sociedade.